Efeitos da sobrepopulação macromolecular no metabolismo celular - Vargas, María Florencia Noriega Romero (2012)
Cellular functions are the result of diverse molecular interactions, many of which occur inside the cell, an enviromnment where 70-90% of dry weight is occupied by macromolecules, whose concentrations depend on cellular metabolism. In this dissertation we develop a model to study if the limited solven capacity in the cell represent a significant constraint on the metabolicorganization, characterized by flows in the reactions. We found two types of metabolic switches, activation and inactivation of metabolic fluxes, when the cell is shifted from low to high growth rates. Such behavior is observed in yeast cells and is called Crabtree effect, where at high growth rates acetate compound is secreted by the cell, indicating the activation of the fermentation pathway of glucose consumption.